Israeli identity : in search of a successor to the pioneer, Tsabar, and settler - Weissbrod, Lilly, 1929- (Routledge, 2013)
This thoroughly researched book reveals the true identity of the modern Israeli. Israelis are unique in having changed their identity three times in only one hundred years. Written in a user-friendly style, the book will appeal to scholars and students of the Middle East.
Keywords: Jews -- Israel -- Identity.; Self-perception -- Israel.; National characteristics, Israeli.; Israel -- Social conditions -- 20th century.; Juifs -- Israël -- Identité.; Perception de soi -- Israël.; Israéliens.; SOCIAL SCIENCE -- Discrimination & Race Relations.; SOCIAL SCIENCE -- Minority Studies.; Jews -- Identity; National characteristics, Israeli; Self-perception; Social conditions; Israel; 1900-1999